2023
DOI: 10.3390/foods12091894
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lard or Plus Soybean Oil on Markers of Liver Function in Healthy Subjects: A Randomized Controlled-Feeding Trial

Abstract: Humans have consumed lard for thousands of years, but in recent decades, it has become much less popular because it is regarded as saturated fat. Animal studies showed that lard plus soybean oil (blend oil) was more advantageous for liver health than using either oil alone. This study aims to assess the effects of blend oil on liver function markers in healthy subjects. The 345 healthy subjects were randomized into 3 isoenergetic diet groups with different edible oils (30 g/day) (soybean oil, lard, and blend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Consistent with the findings of the present study, a previous study reported normal liver and kidney function tests were observed in rats after being fed a KD for 60 days ( 46 ). A recent study reported that liver function markers differ among groups fed lard, soybean oil or a blend of both, with the levels of AST and ALT being lower in subjects that consumed the blend oil for 12 weeks compared with those in subjects in the pure soybean oil or lard groups ( 47 ). The KD composition used in the present study was prepared primarily with lard (84%) and combined with soybean oil, while there was no lard in the CD, which should be taken into consideration for further research.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the findings of the present study, a previous study reported normal liver and kidney function tests were observed in rats after being fed a KD for 60 days ( 46 ). A recent study reported that liver function markers differ among groups fed lard, soybean oil or a blend of both, with the levels of AST and ALT being lower in subjects that consumed the blend oil for 12 weeks compared with those in subjects in the pure soybean oil or lard groups ( 47 ). The KD composition used in the present study was prepared primarily with lard (84%) and combined with soybean oil, while there was no lard in the CD, which should be taken into consideration for further research.…”
Section: Discussionmentioning
confidence: 99%
“…Both fats are dominated by lauric acid (C12:0) with up to 50% content of all fatty acids [37,39]. In turn, despite a higher content of SFA, insect fat is characterized by a lower content of palmitic (C16:0), stearic (C18:0), and oleic (C18:1 n-9c) acids compared to, e.g., tallow [40] or lard [41]. But what is worth emphasizing, the presence of lauric acid in insect fat seems to be interesting, as medium-chain fatty acids are preferred in energy utilization compared to long-chain saturated or unsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%